Towards better control of chemical risks associated with mining operations in Quebec (Canada) Part 2: Ranking of the potential effects of chemicals on the health of mining workers - Biyick, Paul-Patrice; Badri, Adel; Gauthier, François (International review of applied sciences and engineering (Online), 2023)
The mining industry, currently undergoing profound changes, is destined to play an increasingly important economic role in the province of Quebec, Canada. Activity in this sector, its real net impact on government tax revenue, the economy, society, and the creation of wealth, is the subject of much discussion. Occupational health and safety is a major preoccupation in the mining sector, in which considerable numbers of workers suffer workplace accidents or occupational diseases due to the use of industrial chemicals, compounding the problem of exposure to noxious substances that exist naturally in mines or are produced inevitably in the course of normal mining operations. Air in mines thus can become laden with a wide variety of chemical agents, in the form of suspended solids, liquid droplets, and vapors and gases. Long-term exposure to most of these agents can seriously harm the health of mineworkers. Prevention remains the key to avoiding the social and economic consequences of these hazards and will make mining a more attractive sector for investment and employment in Canada. The principal focus of this study, presented in two articles, is to set a preliminary theoretical framework for categorizing chemicals in terms of their effects on the health of mineworkers throughout the various phases of mining projects. The objective is to decrease (over the long term) the number of occupational diseases due to the use of chemicals by raising awareness among employers and exposed workers in the mining sector. This research was conducted in four phases. The first article presented a review of the literature [1] on the chemical aspects of health and safety in mining in the province of Quebec. In the present article, the findings on the recurrence of health problems attributable to chemicals encountered in mines and how these effects should therefore be ranked from an occupational health and safety perspective are presented. The results show that various forms of dermatitis are the most recurrent health and safety risk.